1972
DOI: 10.1159/000208509
|View full text |Cite
|
Sign up to set email alerts
|

Epsilon-Aminocaproic Acid for Synovectomy in Haemophilic Patients

Abstract: The study of coagulation and fibrinolysis in synovectomised haemophilic patients, treated by a new haemostatic combined therapy, is reported. This treatment is based on a combination of replacement therapy (fresh frozen plasma and/or cryoprecipitates) and ε-aminocaproic acid; the replacement therapy is continued for only 6 days, beginning on the day of operation. Our combined therapy scheme promotes a more efficient haemostasis than substitutive therapy alone and allows a considerable saving in plasma or plasm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

1974
1974
2008
2008

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…EACA has also been used in more extensive surgery in hemophiliacs, such as synovectomy, in an effort to decrease the quantity of Factor VIII replacement [82]. The rationale is identical to that for dental surgery.…”
Section: Use Of Eaca In Congenital Coagulation Defectsmentioning
confidence: 99%
“…EACA has also been used in more extensive surgery in hemophiliacs, such as synovectomy, in an effort to decrease the quantity of Factor VIII replacement [82]. The rationale is identical to that for dental surgery.…”
Section: Use Of Eaca In Congenital Coagulation Defectsmentioning
confidence: 99%
“…Use of the antifibrinolytic agent epsilon-aminocaproic acid (EACA) has been recommended as an alternative to replacement material in patients with hemophilia and related disorders who are undergoing surgery. 9 We consider the use of EACA to be contraindicated in the usual patients when adequate replacement therapy is available. The clot formed by EACA on the fibrinogen strands may not lyse for 6 months and thus cause considerable fibrosis.…”
mentioning
confidence: 99%
“…Aminocaproic acid combined with replacement therapy has been used to minimize bleeding during orthopedic surgery on hemophiliacs, for example, in assoeiation with synovectomy (Storti et al 1972). Ahlberg (1970) has shown that aminacaproic acid given intravenously (i.v.)…”
mentioning
confidence: 99%